Taeniid cestodes in a wolf pack living in a highly anthropic holly agro-ecosystem - Fabio Macchioni; Francesca Coppola; Federica Furzi; Simona Gabrielli; Samuele Baldanti; Chiara Benedetta Boni; Antonio Felicioli (Parasite, 2021)
The Italian wolf population in human-modified landscapes has increased greatly in the last few decades. Anthropisation increases the risk of transmission of many zoonotic infections and in this context, control of taeniid cestode species needs to be addressed from a One Health perspective. Predator-prey interactions are at the root of taeniid cestode transmission, and the wolf plays a key role in the maintenance and transmission of taeniids. To date, all available data on the taeniids of wolves in Italy refer to populations living in a wild habitat. Between 2018 and 2019, we investigated taeniids in a wolf pack living in a highly anthropic hilly agro-ecosystem. Thirty-eight faecal samples were collected and analysed, 4 of which were also genetically characterised for individual wolves and belonged to three different animals. Samples collected were analysed microscopically and by molecular analysis in order to identify the taeniid species. Taeniid eggs were detected in 34.2% (13/38) of samples. Within samples positive to taeniid eggs only Echinococcus granulosus s.s. and Taenia hydatigena were identified in 26.3% and 10.5% of the samples, respectively. On microscopic examination, Capillaria spp., Ancylostomatidae and Toxocara canis eggs, Crenosoma vulpis larvae, and coccidian oocysts were also found. The combination of low biodiversity of taeniid species with a high occurrence of E. granulosus s.s. recorded in this study could be the consequence of a deeper link occurring between wolves and livestock in human-modified landscapes than in wild settings